1949
DOI: 10.1084/jem.89.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Serum Disease

Abstract: The intravenous injection of one large dose of serum into rabbits caused a variety of changes of considerable complexity. 1. There was an immediate proliferation of mesenchymal cells, including plasma cells, particularly in heart, lungs, and spleen. 2. The signs of serum disease developed only at the time of abundant antibody formation, before significant quantities of antibody were laid down in the vascular connective tissue. 3. Allergic arteritis, marked glomerula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
9
0

Year Published

1949
1949
1971
1971

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(14 citation statements)
references
References 9 publications
(16 reference statements)
5
9
0
Order By: Relevance
“…Moycarditis.--Areas of necrosis of varying size and similar to those described previously (13) were noted in the right ventricle of about one-half of the rabbits in each group. These lesions are apparently similar to those described by Longcope (19), Apitz (20), and more recently by Ehrich (17).…”
Section: Frequency Of Arterizis In Groups Of Rabbits Receldng Varioussupporting
confidence: 90%
See 2 more Smart Citations
“…Moycarditis.--Areas of necrosis of varying size and similar to those described previously (13) were noted in the right ventricle of about one-half of the rabbits in each group. These lesions are apparently similar to those described by Longcope (19), Apitz (20), and more recently by Ehrich (17).…”
Section: Frequency Of Arterizis In Groups Of Rabbits Receldng Varioussupporting
confidence: 90%
“…On the basis of our findings it seems probable that there are two types of glomerular lesions following the injections of foreign serum as Ehrich eta/. (17) have recently claimed. One is a focal necrotizing glomerulitis which is found in rabbits receiving any one of several of the serum fractions and the other a diffuse transient glomerular lesion which occurs relatively soon and particularly after the injection of the serum globulins.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…To indicate further the possible immunologic character of the vascular lesions of hypersensitivity, we demonstrated, in con junction with Cohen (253), that these vascular lesions may well be induced in normal recipients (rabbits) by passive sensitization. By this technique one could eliminate the possibility that the patho logic changes are induced, as has been supposed (254)(255)(256)(257)(258)(259), by the toxic or non-specific action accompanying administration of large doses of foreign serum. Chemical agents interfere with tins effect of passive sensitization (260) ; thus a strong relation seems to exist between the collagen diseases and hypersensitivity (261,262).…”
Section: Experimental Evidence Of Hypersensitivity As a Basismentioning
confidence: 99%
“…(Received for publication, March 8, 1952) In a previous publication it was shown that acute diffuse glomerulonephritis develops in rabbits injected intravenously with large quantities of purified bovine serum gamma globulin (1). Other investigators have produced experimental glomerulonephritis by giving animals intravenous injections of either normal horse serum (2)(3)(4)(5)(6), normal duck serum (4), a number of "antikidney sera" (7)(8)(9)(10)(11)(12)(13)(14)(15), antiplacenta serum (16), or horse (17) or bovine (1,18) serum gamma globulins. The number of these substances, and the variety of technics employed in their use, at once suggest that if a single pathogenetic explanation is valid for the glomerulonephritis in all cases, it must bring into harmony the differences in experimental procedures.…”
mentioning
confidence: 99%